2019
DOI: 10.1259/dmfr.20180340
|View full text |Cite
|
Sign up to set email alerts
|

Influence of scan mode (partial/full rotations) and FOV size in the formation of artefacts in cone beam CT

Abstract: To evaluate the influence of rotation degree and field of view (FOV) size on the amount of artefacts produced in cone beam CT (CBCT) images. methods: A cylindrical wax utility phantom, with a metallic sample in its interior, was scanned with two FOV sizes (100 x 100 and 40 x 40 mm) and in full (360°) and partial (~180°) rotations. After the acquisitions, images were objectively assessed in the ImageJ software, obtaining the standard deviation in areas around the metal sample. The influence of artefacts produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Second by the inaccuracy of the examiner using the computer mouse; which has been previously demonstrated that the average precision error between the on-screen cursor and the mouse displacement was 0.018 mm² (16)(17)(18). This measurement error may not be suitable for precise control applications, however, this may be precise enough for a successful CBCT linear measurements, as representing less than a voxel size currently used (13,(16)(17)(18). Further studies are needed to clarify the clinical relevance of these narrow ranges, using another CBCT scanner with a smaller voxel size may allow a more accurate measurement (18).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Second by the inaccuracy of the examiner using the computer mouse; which has been previously demonstrated that the average precision error between the on-screen cursor and the mouse displacement was 0.018 mm² (16)(17)(18). This measurement error may not be suitable for precise control applications, however, this may be precise enough for a successful CBCT linear measurements, as representing less than a voxel size currently used (13,(16)(17)(18). Further studies are needed to clarify the clinical relevance of these narrow ranges, using another CBCT scanner with a smaller voxel size may allow a more accurate measurement (18).…”
Section: Discussionmentioning
confidence: 98%
“…Currently, some studies have introduced CBCT imaging to evaluate dentin thickness before and after fractured instrument removal (7,13), or before and after root canal preparation (20,21). However, no comparisons with a reference standard were reported, which prevents accuracy from being determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the FOV exposes more tissues to x-rays, increases scattered radiation to the surrounding tissues, decreases contrast, and increases noise and radiation dose [ 14 , 20 , 21 ]. Scatter might be reduced by reducing FOV as well as the use of an anti-scatter grid and algorithms to correct the x-ray scatter [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…CBCT scanning with 360-degree rotation compared to the standard 180-degree scan enhances the image quality by creating more basis images. Enhancement of rotation range increases the CNR, but despite the larger amount of data, changing the device rotation range does not affect the number of artifacts (e.g., beam hardening, scatter, and ring artifacts) that occur both in 180- and 360-degree scans [ 7 , 21 , 26 ].…”
Section: Reviewmentioning
confidence: 99%